Characterization of the tree component associated with the camedor palm cultivation in the Selva Lacandona, Chiapas, Mexico - Sánchez-Gutiérrez, Facundo; Beltrán-Rodríguez, Leonardo; Valenzuela-Gómez, Chankin; Martínez-Valdés, Martín Gerardo; González-González, Carlos Alejandro; Monroy-Hernández, Rubén (Ecosistemas y Recursos Agropecuarios, 2025)
Tree structure, composition and diversity used for shade in traditional agroforestry systems (SAF) of Chamaedorea ernesti-augusti H. Wendl.), with ages of one to five years, in the Puerto Bello Metzabok community,Selva Lacandona, Mexico, were characterized. In each age group, two sampling units (MU) of 600 m2 were randomly established. The normal diameter (DN) and height of trees with DN ≥ 2 cm were measured. Tree composition and structure were determined through the importance value index (IVI) and forest index (IVF), and diversity was evaluated with Shannon-Wiener (H’), Simpson (D) and Fisher’s Alpha (α) indexes. A total of 947 individuals belonging to 93 species, and distributed in 82 genera and 44 families were recorded, on wich seven are catalogued in NOM-059-SEMARNAT-2010. An mean of 1 578 individuals. ha-1 were registered, with an average of 12.1 cm in DN and 11.4 m in height. The species with the highest IVI and IVF values were Trichospermum mexicanun, Lonchocarpus salvadorensis, Nectandra salicifolia and, Dendropanax arboreus. The three-year SAF recorded greater species diversity (H´ = 3.76, D = 0.94 y α = 22.24). These findings ongoing valuable information about the structural importance in the first stages of ecological succession of shade trees used in the production of a non-timber forest product of high economic importance in the region, which constitutes a useful tool for its sustainable management.